2021
DOI: 10.1016/j.nahs.2021.101090
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of switched homogeneous time-delay systems under synchronous and asynchronous commutation

Abstract: In this work, stability analysis for a class of switched nonlinear time-delay systems is performed by applying Lyapunov-Krasovskii and Lyapunov-Razumikhin approaches. It is assumed that each subsystem in the family is homogeneous (of positive or negative degree) and asymptotically stable in the delay-free setting. The cases of existence of a common or multiple Lyapunov-Krasovskii functionals and a common Lyapunov-Razumikhin function are explored. The scenarios with synchronous and asynchronous switching are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Studies involving different time delays can be found in ship stabilization, control processes for pressure, and heat transfer regulation, but they are sometimes deliberately introduced into feedback systems to improve system performances see [1,5] and references therein for details. See also [6,7,8], and [9] for more details on system performances in the presence of time delays.…”
Section: Original Research Articlementioning
confidence: 99%
“…Studies involving different time delays can be found in ship stabilization, control processes for pressure, and heat transfer regulation, but they are sometimes deliberately introduced into feedback systems to improve system performances see [1,5] and references therein for details. See also [6,7,8], and [9] for more details on system performances in the presence of time delays.…”
Section: Original Research Articlementioning
confidence: 99%
“…Two illustrative examples are shown in Section 5. A conference version of this paper is restricted to disturbance-free analysis of the scalar systems 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The research results for time-delay systems are numerous. In order to investigate the stability of switched time-delay systems, the Lyapunov–Krasovskii functions 19 , 20 , average dwell time (ADT) method 21 , neural network-based adaptive control 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%